1988
DOI: 10.1016/0304-3959(88)90197-2
|View full text |Cite
|
Sign up to set email alerts
|

Substance P in CSF of patients with chronic pain syndromes

Abstract: Immunoreactive substance P was determined in lumbar CSF of 35 healthy volunteers and 60 patients with chronic pain syndromes of at least 6 months duration. No significant relationships were found between substance P levels and age, sex or body height. Substance P levels were lower in chronic pain patients, with either neurogenic (n = 23) or idiopathic pain (n = 37) syndromes, than in the healthy volunteers. Substance P levels were especially low in patients with neurogenic pain with lesions involving the extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 20 publications
2
18
2
2
Order By: Relevance
“…Previous human studies report no gender differences in SP cerebrospinal fluid concentrations or in NK1R binding in post-mortem brain studies (Almay et al, 1988 ;Burnet and Harrison, 2000 ;Carletti et al, 2005). In contrast to our hypothesis, our data on NK1R binding shows that on average women have generally lower brain NK1R-BP compared to men.…”
Section: Gender and Nk1rscontrasting
confidence: 86%
“…Previous human studies report no gender differences in SP cerebrospinal fluid concentrations or in NK1R binding in post-mortem brain studies (Almay et al, 1988 ;Burnet and Harrison, 2000 ;Carletti et al, 2005). In contrast to our hypothesis, our data on NK1R binding shows that on average women have generally lower brain NK1R-BP compared to men.…”
Section: Gender and Nk1rscontrasting
confidence: 86%
“…This facilitation is triggered by the pre-synaptic release of neurotransmitters and neuromodulators such as glutamate [23,24], substance P [25,26], brain derived neurotrophic factor (BDNF) [27] and prostaglandins [28,29]. These neurotransmitters and neuromodulators activate ligand-gated ion channels (NMDA-receptor-glutamate) [26], metabotrophic receptors (metabotrophic glutamate receptor (mGluR)-glutamate and NK1-substance P [30]) and tyrosine kinase receptors (Tyrosine Kinase (Trk) B-BDNF [27]) and increase intracellular calcium via release from intracellular stores and calcium inflow [20] (Fig. 1).…”
Section: Spinal Mechanismsmentioning
confidence: 99%
“…An earlier report [77] indicated that substance P was lower than normal in a variety of chronic painful conditions such as low back pain. In two studies, cerebrospinal fluid substance P was lower than normal in diseases involving idiopathic pain [78] and in chronic neurogenic pain syndromes, including diabetic neuropathy [79]. Finally, both cerebrospinal fluid substance P and cerebrospinal fluid met-enkephalin were normal in chronic pain patients [80].…”
Section: Substance Pmentioning
confidence: 99%